2017
DOI: 10.31018/jans.v9i4.1511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Homa organic farming on growth, yield and quality parameters of Okra

Abstract: A field experiment was conducted during kharif season of 2012 to study the biochemical efficacy of Homa organic farming practices in okra (Abelomoschus esculentus var. Arka Anamika) and laid out in randomized block design with 18 treatments replicated thrice. The treatments consist of control treatments i.e. conventional control and homa control; homa treatments (Agnihotra and Om Tryambakam homa) and non-homa treatments; and liquid organic manures viz, Panchagavya, Jeevamruta and Gloria Biosol for soil and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…Other qualitative attributes were also greatly influenced by the Vedic and Agnihotra Farming over the absolute control and findings revealed significant effect of Agnihotra farming over TSS (ºBrix), reducing sugar (%), total sugar (%) and ascorbic acid (mg 100 g -1 ) than respective other counterparts (Table 2). Such findings especially in the case of homa induction (Agnihotra Farming) clearly supported the capability of homa farming on enhancing rhizosphere and biosphere simultaneously (Pathak and Ram, 2010) and higher level of ascorbic acid in homa induced growing conditions as recorded in the present investigation corroborated well with the previous findings of Kumar et al (2017).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Other qualitative attributes were also greatly influenced by the Vedic and Agnihotra Farming over the absolute control and findings revealed significant effect of Agnihotra farming over TSS (ºBrix), reducing sugar (%), total sugar (%) and ascorbic acid (mg 100 g -1 ) than respective other counterparts (Table 2). Such findings especially in the case of homa induction (Agnihotra Farming) clearly supported the capability of homa farming on enhancing rhizosphere and biosphere simultaneously (Pathak and Ram, 2010) and higher level of ascorbic acid in homa induced growing conditions as recorded in the present investigation corroborated well with the previous findings of Kumar et al (2017).…”
Section: Resultssupporting
confidence: 92%
“…However, more yield (72.37 t ha -1 ) recorded under E 2 C 1 [Enriched Sanjeevani (1%) + Homa Induction (Agnihotra)] followed by only 30.29 t ha -1 in E 2 C 2 [Only Homa Induction (Agnihotra)] growing condition (Table 1). This type of findings may probably be due to the synergistic impact of the integration of organic farming and Homa farming as Homa Jaivik Krishi (Pathak, 2009) and the higher level of yield as recorded here close conformity with the earlier observation of Kumar et al (2017) where they observed better growth and yield in okra grown through Homa Organic treatments. Besides, in homa farming condition the chlorophyll of the plants are increased, and those are the main cause of the faster growth and yield maximization (Berk and Jhonson, 2009).…”
Section: Resultssupporting
confidence: 89%
“…Soil has been polluted by various toxic compounds and homa therapy has the power to rejuvenate the soil by maintaining a healthy micro flora and fuauna [18] . Studies have also demonstrated that homa organic treatments enhanced crop productivity and quality [19][20] . Application of homa treatment, smoke and ash makes the soil rich in terms of soil micro flora and macro and micronutrient i.e.…”
Section: Effect Of Homa Therapy On Disease Initiation and Developmentmentioning
confidence: 99%